Distance to highway and factory density related to lung cancer death and associated spatial heterogeneity in effects in Jiading District, Shanghai - Zhang, Na; Wang, Yingjian; Yu, Hongjie; Zhang, Yiying; Xiang, Fang; Jiang, Honglin; Zheng, Yingyan; Xiong, Ying; Wang, Zhengzhong; Chen, Yue; Jiang, Qingwu; Shao, Yueqin; et al. (Environmental science and pollution research international, 2021)
This study aimed to determine the spatial effects of traffic- and industrial-related pollution on the mortality for lung cancer (LC). We conducted a retrospective cohort study by using the data from LC registry in Jiading District for the period from 2002 to 2012. Standard parametric model with Weibull distribution was used for spatial survival analysis. Shorter distance to highway (adjusted odds ratio (aOR) = 1.15, 95% confidence interval (CI): 1.03–1.30) and higher factory density (aOR = 1.20, 95% CI: 1.05–1.37) were significantly associated with an increased risk of LC death, and there was a spatial difference in the associations between northern and southern areas of Jiading District. The risk was high in suburbs as compared with urban areas. Traffic- and industrial-related pollution were significantly associated with an increased risk of LC death, which showed a spatial variation. Further studies are needed to better understand the current LC status in the suburbs and to reduce health disparities.